2009
DOI: 10.1186/1741-7015-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of the probability of return of spontaneous circulation in intervals without chest compressions during out-of-hospital cardiac arrest: an observational study

Abstract: Background: One of the factors that limits survival from out-of-hospital cardiac arrest is the interruption of chest compressions. During ventricular fibrillation and tachycardia the electrocardiogram reflects the probability of return of spontaneous circulation associated with defibrillation. We have used this in the current study to quantify in detail the effects of interrupting chest compressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…141,[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166] No prospective human studies have specifically evaluated whether treatment altered by predicting success of defibrillation can improve successful defibrillation, rate of ROSC, or survival from cardiac arrest. The value of VF waveform analysis to guide management of defibrillation in adults with in-hospital and out-of-hospital cardiac arrest is uncertain (Class IIb, LOE C).…”
Section: Vf Waveform Analysis To Predict Defibrillation Successmentioning
confidence: 99%
“…141,[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166] No prospective human studies have specifically evaluated whether treatment altered by predicting success of defibrillation can improve successful defibrillation, rate of ROSC, or survival from cardiac arrest. The value of VF waveform analysis to guide management of defibrillation in adults with in-hospital and out-of-hospital cardiac arrest is uncertain (Class IIb, LOE C).…”
Section: Vf Waveform Analysis To Predict Defibrillation Successmentioning
confidence: 99%
“…48,49 The quality, depth, and rate of compressions and the duration of interruptions to compressions have a direct impact on outcome of cardiac arrest. 5,8,[62][63][64][65][66][67][68][69] Performance of high-quality chest compressions should therefore be the core psychomotor skill taught in any CPR training program, with emphasis on correct depth and rate, full chest recoil, and minimal interruptions in compressions. When teaching hands-only CPR for adults who have suddenly collapsed, providing high-quality chest compressions is the only psychomotor skill that needs to be taught.…”
Section: Providing High-quality Chest Compressionsmentioning
confidence: 99%
“…As previously mentioned, it has been shown that pauses in pre-shock CPR as short as 3 s decrease the mean probability of ROSC by approximately 23% 8. As CPR continues to be performed there is a noticeable decrease in the quality of CPR that is being performed by EMS personnel,25 which could lead to a more widespread use of automatic CPR devices.…”
Section: Discussionmentioning
confidence: 98%